2014
DOI: 10.1074/jbc.m114.587170
|View full text |Cite
|
Sign up to set email alerts
|

E2F Transcription Factor 1 Regulates Cellular and Organismal Senescence by Inhibiting Forkhead Box O Transcription Factors

Abstract: Background: E2F1 and FOXO3 are two transcription factors participating in cellular senescence. Results: E2F1 represses FOXO3 transactivity through interaction. Conclusion: E2F1-FOXO3 regulatory mechanism is conserved and participates in regulating cellular senescence. Significance: Drugs and/or therapies that inhibit the physical interaction might be candidates for reducing cellular senescence and increasing longevity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 34 publications
2
28
0
Order By: Relevance
“…16g). Moreover, the same result was later reported by another group in connection with daf-16 regulation, both in C. elegans and in a mammalian system (Xie et al 2014 We have already given an overview and provided some data on transcription factors with the main function during development that have a large effect on lifespan when downregulated or upregulated post developmentally. One more such transcription factor, ceh-22/F29F11.5, has been studied in connection with hlh-2/M05B5.5 and fits the same paradigm of the developmental theory of aging.…”
supporting
confidence: 78%
“…16g). Moreover, the same result was later reported by another group in connection with daf-16 regulation, both in C. elegans and in a mammalian system (Xie et al 2014 We have already given an overview and provided some data on transcription factors with the main function during development that have a large effect on lifespan when downregulated or upregulated post developmentally. One more such transcription factor, ceh-22/F29F11.5, has been studied in connection with hlh-2/M05B5.5 and fits the same paradigm of the developmental theory of aging.…”
supporting
confidence: 78%
“…Conserved targets also exhibited enrichment for E2F, bZIP, and NFY motifs. Interestingly, E2F regulates cellular senescence in mammalian cells, and E2F ( efl‐1 ) knockout in C. elegans extends lifespan in a daf‐16 ‐dependent manner (Xie et al ., ). Intriguingly, the bZIP family of transcription factors includes CREB, which has been implicated in lifespan regulation and loss of learning and memory with age in worms (Kauffman et al ., ; Mair et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…In human fibroblasts, E2F-1 enhances cellular senescence, whereas FoxOs antagonize senescence by upregulating the formation of ROS scavenging proteins [154,155] . Xie et al [156] showed that E2F-1 attenuates FoxO3a-mediated expression of MnSOD and catalase. They mapped interaction between E2F-1 and FoxO3a to a region including the DNA binding domain of E2F-1 and the C-terminal transcription activation domain of FoxO3a.…”
Section: Redox Regulation Of Foxo Expressionmentioning
confidence: 99%
“…They mapped interaction between E2F-1 and FoxO3a to a region including the DNA binding domain of E2F-1 and the C-terminal transcription activation domain of FoxO3a. They propose that E2F-1 inhibits FoxO3a function by directly binding FoxO3a in the nucleus and preventing the activation of its target genes [156] . Depending on the cellular and promoter context (and possibly also on the redox conditions in the cell), the two proteins can therefore act synergistically, or one can antagonize the activity of the other.…”
Section: Redox Regulation Of Foxo Expressionmentioning
confidence: 99%